An Analysis of Sociogenesis Motive of Main Character in “Unbroken” Movie - Juwita Boneka Sinaga (English Department, University of Riau Kepulauan, Batam,Indonesia, 2017)
This research entitled “An Analysis of Sociogenesis Motive of Main Character in ‘Unbroken’ movie. It discussed the socio genesis of the main character in the movie